STRATEGI ADAPTASI KEARIFAN LOKAL MASYARAKAT NELAYAN TERHADAP PERUBAHAN EKOSISTEM PESISIR ACEH - Arfriani Maifizar (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
This study includes the importance of maintaining local wisdom by fishing communities in the face of adaptation to the impact of ecosystem changes on Sabang Island. Through deepening of the literature review, in-depth interviews, observations, and focus group discussions were conducted with local fishing communities in the coastal area of Sabang Island, finally found some research results that made reference to the adaptation strategies that fishermen community carried to the impact of ecosystem changes through local wisdom. The results show that Sabang Island fishermen communities who have felt the impact of ecosystem changes such as mangrove damage, coral reefs due to exploitation of coastal resources and natural disasters can achieve the success of solving the problem in several ways either through knowledge about adaptation made by fishing communities obtained from academic knowledge, or through knowledge that has been entrusted in a downward manner known as local wisdom. Therefore, fisherman adaptation strategies in addressing the impacts of ecosystem change follow a pattern of reactive adaptation, they tend to use capabilities from within the community. This adaptation pattern is carried out by developing job diversification, modifying the fleet of boats and taking action with the community in rehabilitating damaged ecosystems and the role of commander laot to the fishermen in arranging the time of catching with the natural sign through the knowledge of inheritance as local wisdom that needs to be maintained all the time. Keyword: Fisherman Society, Adaptation, ecosystem change, local wisdom.